HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI TERHADAP KEMAMPUAN SMASH KEDENG ATLET SEPAKTAKRAW PADA CLUB GEMILANG JAYA PEKANBARU - Regi Masrizal; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The Problem in this research is a kedeng smash performance of athlete at Gemilang Jaya Sepaktakraw Club Pekanbaru were still lack of improvement, so that they often missed and ball go out of the field, caused of the smash missed by the players is the lack of leg mucle explosive power and eye-and-foot coordination of the ball floating in the air. In this research aims to find out wether there is the any correlation between limb muscle explosive power and eye-and-foot coordination on kedeng smash performance at Gemilang Jaya Sepaktakraw Club Pekanbaru. The type of this research is Multiple Correlation which has aims to find out level of coordination of different variables. The Technique of sampling is representative athletes at Gemilang Jaya Sepaktakraw Club Pekanbaru who can truly represent, which consisted of 6 athletes. This research was conducted at field of Gemilang Jaya Sepaktakraw Club Pekanbaru. The Instrument used in this research was limb muscle explosive power, eye and foot coordination, and kedeng smash performance. The collected data were analyzed by using multiple correlation. Based on the data analysis and discussion before showed that was proven with TCount is 0.67 and Ttable is 0.319. It means Tcount > Ttabel in the level ɑ= 0.05. It can be concluded that there is the any correlation between limb muscle explosive power and eye-and-foot coordination on kedeng smash performance at Gemilang Jaya Sepaktakraw Club Pekanbaru. In other words, the alternative hypothesis of this research was accepted.Key Words: Limb Muscle Explosive Power, Eye and Foot Coordination, Kedeng Smash Performance.